The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3341/kjo.2019.0105
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of Manual Measurement of Foveal Avascular Zone Area in Optical Coherence Tomography Angiography Images in High Myopia

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses /by-nc/3.0/) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. 113 Original ArticleHigh myopia is one of the most common causes of visual loss and is especially common in Asia. The prevalence of myopia is as high as 80% in Asia and 25% in other regions [1][2][3]. Severe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…This biological association between FAZ parameters and refractive has already been reported in various studies. 17–20 Although we have made corrections for AL-related magnification to take account of FAZ parameters, these variations alone may not have been the effect of biological associations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This biological association between FAZ parameters and refractive has already been reported in various studies. 17–20 Although we have made corrections for AL-related magnification to take account of FAZ parameters, these variations alone may not have been the effect of biological associations.…”
Section: Discussionmentioning
confidence: 99%
“…This biological association between FAZ parameters and refractive has already been reported in various studies. [17][18][19][20] Although we have made corrections for AL-related magnification to take account of FAZ parameters, these variations alone may not have been the effect of biological associations. In our study, the mean SFCT was 309.47 ± 68.39 μm (Range: 192 to 417 μm) and 308.31 ± 69.36 (Range: 196 to 420 μm), respectively, in right eye and left eye with a mean SFCT between two eyes of 308.89 ± 68.87 μm.…”
Section: Variation Faz Parameters With Ocular and Systemic Parametersmentioning
confidence: 99%
“…Fang et al [ 17 ] reported that FAZ area measurements using OCTA exhibited excellent repeatability and correlation in healthy eyes and that the ICC associated with FAZ area measurements was 0.961. Lee et al [ 18 ] reported that the repeatability of manual FAZ area measurements was good in high myopia patients. The ICC associated with the SFAZ area measurements was 0.891 and the CV was 8.8%, and those associated with the DFAZ were 0.788 and 11.2%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of research into the patterns and mechanisms of FAZ area changes in high myopia are inconclusive [6] . During the process of high myopic axial lengthening, the eyeballs do not uniformly expand to maintain the spherical shape [22]; the difference in the length of the high myopia axis leads to different degrees of optical magni cation, and current OCTA equipment does not provide correction methods [23]. This may affect the accuracy of the FAZ area of highly myopic eyes, resulting in discrepancies.…”
Section: Discussionmentioning
confidence: 99%
“…The inner layer of the retina is mainly composed of the nerve ber layer and the ganglion cell layer. The OP wave [22] mainly re ects the condition of the microcirculation of the retinal inner layer. As the degree of myopia increases, the blood ow density of the super cial microcirculation decreases, the OP wave amplitude is reduced, and the function of the inner retina is weakened.…”
Section: Correlation Of Macular Microcirculation Macular Structure and Electrophysiological Function In People With High Myopiamentioning
confidence: 99%